A memória escrita: três estudos comparativos sobre João Cabral e Marcel Proust - Vieira, Thales Rodrigo (2020)
This study analyzes the confluence of João Cabral de Melo Neto’s poetry from the book A Escola das Facas on and Marcel Proust’s novel, À la recherche du temps perdu, comparing the aspect of memory in its varied manifestations. First, we tried to retrace some reconfigurations of memory in João Cabral’s works that allowed the dialogue between João Cabral’s final production and Marcel Proust’s greatest work. The author of A Escola das Facas evokes Pernambuco from his memories, just as Marcel Proust portrays Paris and the places in the French province of his memories. In order to broaden the understanding of written memory in the two authors, we divided our research into three parts. The first deals with the philosophical aspects of memory in both authors. The second analyzes the written memory of João Cabral and Proust as a set of Short stories told by the anecdotal genre. Finally, the third part analyzes the historical and social aspects of the memory of the two authors, that is, memory as a passage of historical time. In João Cabral, the memory of the end of the monoculture world of the Pernambuco sugar cane mills; in Proust, the memory of the late 19th century in France and the end of the Belle Époque and the collapse of the power of the French aristocracy.